Acupuncture benefits to women with recurrent implantation failure: A propensity score-matched cohort study - Di Gan; Li-Ying Liu; Ying Zhong; Yong-Na Wu; Yuan-Yuan Lai; Wei Wei; Xiao-Li Guo; Rui Tian; Si-Yi Yu; Fan-Rong Liang; Wen-Hui Hu; Jie Yang (Heliyon, 2023)
Objectives: The current study aims to assess the effectiveness of acupuncture in improving the live birth rate (LBR), ongoing pregnancy rate (OPR), clinical pregnancy rate (CPR), biochemical pregnancy rate (BPR), and pregnancy loss (early abortion rate, late abortion rate, ectopic pregnancy rate) in patients with recurrent implantation failure (RIF). Design: This retrospective study compares the outcomes of patients with RIF who underwent frozen embryo transfer (FET) with or without acupuncture. Setting: The medical records of patients diagnosed with RIF and visiting Chengdu Xi'nan Gynecological Hospital between January 2018 and June 2021 were reviewed. The Chengdu Xi'nan Gynecological Hospital Ethics Committee approved this retrospective study (No. 2021–029). Participants: A total of 923 patients with RIF who underwent FET were included in this study. The patients were divided into two groups: the Acupuncture (n = 303) and the Non-acupuncture groups (n = 620). Exposure: The Acupuncture group consisted of 303 RIF patients who received acupuncture therapy in addition to standard hormone replacement therapy (HRT)/delayed hormone replacement therapy (d-HRT) for FET. The Non-acupuncture group consisted of 620 RIF patients who received only standard HRT/d-HRT for FET. Primary and secondary outcome measures: The primary outcome was the LBR. The secondary outcome referred to OPR, CPR, BPR, and pregnancy loss. Results: The Acupuncture group had significantly higher BPR (P = 0.08) and CPR (P = 0.049) than the Non-acupuncture group. A potentially higher LBR (P = 0.16) and OPR (P = 0.248) were observed in the Acupuncture group than in the Non-acupuncture group. However, the survival analysis did not show that acupuncture significantly promoted live birth. Conclusions: Acupuncture is an appropriate adjunctive technique in the in vitro fertilization process as it improves biochemical and clinical pregnancies. Therefore, it is necessary to be cautious about the role of acupuncture throughout the whole pregnancy cycle.